nalysis of Customer Satisfaction on Service Quality at ‘TRANS JOGJA’Bus Stop Using a SERVQUAL (Service Quality) and House of Quality (HOQ) - Clea Putri, Famelga; Riana, Riska Iva; Herdianzah, Yan (Journal of Industrial System Engineering and Management, 2024)
Yogyakarta is a city that is often called a miniature of Indonesia, has a multitude of features. Starting from governance to many other features. Trans Jogja is one of the BRT products for the city of Jogja which is said to have been initially built to provide clean, neat and comfortable city transportation for everyone. However, Trans Jogja, which is heralded as an improvement in public transportation service modes, is in reality still less than optimal. In order to meet the expectations of prospective passengers at bus stops, service improvements and innovations are needed. In this research, Trans Jogja bus stops will be identified using the SERVQUAL and House of Quality methods. The cause of customer dissatisfaction in the Servqual analysis is that from the results of data processing it was found that there was a gap in all service dimensions at the Trans Jogja bus stop. Determining the highest to smallest improvement priorities to increase customer satisfaction in the House of Quality analysis is conducting training to improve performance, evaluating staff performance, updating schedules and daily departure routes clearly and in detail, controlling the availability of service facilities, implementing SOPs for staff , Providing a box for suggestions and criticism, and Providing supporting facilities for the safety and smooth running of Trans Jogja bus stop users.